Pengaruh Kompensasi dan Pengembangan Karir Terhadap Kinerja Karyawan di PT IDS Medical Systems Indonesia: The Impact of Compensation and Career Development on Employee Performance at PT IDS Medical Systems Indonesia - Zasmika Fahira; Tri Lestari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
The importance of human resources in achieving organizational goals, where employee performance is strongly influenced by compensation and career development factors. The purpose of this study was to determine the effect of compensation and career development partially or simultaneously on employee performance at PT IDS Medical Systems Indonesia. The research method used is a quantitative approach with a survey research design. The population in this study were 75 employees of PT IDS Medical Systems Indonesia, and the sampling technique used is incidental sampling, which is a sampling technique based on chance, namely anyone who happens to meet the researcher can be used as a sample if it is deemed that the person who happened to be met is suitable as a data source. Data were collected through questionnaires distributed to respondents. The data analysis method used is multiple linear regression analysis. The results showed that compensation had no significant effect on employee performance, with a significance value of 0.209, while career development had a positive and significant effect on employee performance with a significance value of 0.001. In addition, simultaneous testing shows that there is a positive and significant influence between compensation and career development on employee performance. The conclusion of this study is that although compensation does not have a significant effect directly, career development is proven to have a significant impact on employee performance. Therefore, companies are advised to improve compensation and career development programs in order to improve overall employee performance.